Stimulation of Epithelial Sodium Channels in Endothelial Cells by Bone Morphogenetic Protein-4 Contributes to Salt-Sensitive Hypertension in Rats. (28th October 2020) - Yang, Xu; Niu, Na; Liang, Chen; Wu, Ming-Ming; Tang, Liang-Liang; Wang, Qiu-Shi; Lou, Jie; Song, Bin-Lin; Zheng, Wei-Wan; Ma, He-Ping; Zhang, Zhi-Ren
Abstract : Previous studies have shown that high salt induces artery stiffness by causing endothelial dysfunction via increased sodium influx. We used our unique split-open artery technique combined with protein biochemistry and in vitro measurement of vascular tone to test a hypothesis that bone morphogenetic protein 4 (BMP4) mediates high salt-induced loss of vascular relaxation by stimulating the epithelial sodium channel (ENaC) in endothelial cells. The data show that high salt intake increased BMP4 both in endothelial cells and in the serum and that exogenous BMP4 stimulated ENaC in endothelial cells. The data also show that the stimulation is mediated by p38 mitogen-activated protein kinases (p38 MAPK) and serum and glucocorticoid-regulated kinase 1 (Sgk1)/neural precursor cell expressed developmentally downregulated gene 4-2 (Nedd4-2) (Sgk1/Nedd4-2). Furthermore, BMP4 decreased mesenteric artery relaxation in a benzamil-sensitive manner. These results suggest that high salt intake stimulates endothelial cells to express and release BMP4 and that the released BMP4 reduces artery relaxation by stimulating ENaC in endothelial cells. Therefore, stimulation of ENaC in endothelial cells by BMP4 may serve as another pathway to participate in the complex mechanism of salt-sensitive (SS) hypertension.